Bitcoin's legal and comparative position in Iranian law - amir mohsen shaabani; mohammad mohseni dehkalani; saaed ebrahimi (پژوهشنامه حقوق تطبیقی, 2020)
Transactions have always been one of the vital necessities of human beings, and human beings have always dealt with different types of innovations in order to benefit and use innovative methods in transactions, because the basis of transactions is always based on the basic principle of "exchangers". The contract form is between the two sides of the deal, and it's no secret that the tech world is evolving day by day. Every day in cyberspace, we are facing new and fresh ideas, and various speculations have been made about the situation of Bitcoin in Iran so far.However, no scientific research has been done in this regard. Therefore, the issue of bitcoin has been raised in Iran for a short time, and there are many legal loopholes for legalizing bitcoin in the country, as well as providing bitcoin conditions to prevent many problems, including tax evasion and money laundering. In order to explain the status of bitcoin in law and economics, it is necessary to adopt a policy on the subject of bitcoin and pay attention to the legislature and electronic payment system according to the laws and upstream documents and the position and laws of other countries in the field of bitcoin.